ANALISIS NILAI TAMBAH DAN KEUNTUNGAN AGROINDUSTRI EMPING MELINJO DI DESA BERNUNG KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Tiya Ayu Lestari; Muhammad Irfan Affandi; Adia Nugraha (Lampung University, 2020)
This study aims to analyze added value and profits of melinjo chips agroindustry in Bernung Village. This research was conducted in five melinjo chips agroindustries in Bernung Village, Gedong Tataan Subdistrict, Pesawaran Regency. Data collection was conducted in January 2019. The data were analyzed using qualitative sis and quantitative descriptive analyses. The calculation of added value used Hayami added value method. There are two types of added value of melinjo chips such as uncooked melinjo chips and cooked melinjo chips. The results showed that added value is a positive value, meaning that both kinds of chips agroindustries are feasible to be developed. The value added of uncooked melinjo chips is higher than that of cooked chips. The R/C over total cost is 1.20, meaning that the emping melinjo agroindustry in Bernung Village, Gedong Tataan Subdistrict, Pesawaran Regency is a profitable and viable business since R/C value is more than one.Key words: added value, melinjo chips, profit